Doxorubicin Induces Inflammatory Modulation and Metabolic Dysregulation in Diabetic Skeletal Muscle - Supriya, Rashmi; Tam, Bjorn T.; Pei, Xiao M.; Lai, Christopher W.; Chan, Lawrence W.; Yung, Benjamin Y.; Siu, Parco M. (Frontiers in Physiology, 2016)
Anti-cancer agent doxorubicin (DOX) has been demonstrated to worsen insulin signaling, engender muscle atrophy, trigger pro-inflammation, and induce a shift to anaerobic glycolytic metabolism in skeletal muscle. The myotoxicity of DOX in diabetic skeletal muscle remains largely unclear. This study examined the effects of DOX on insulin signaling, muscle atrophy, pro-/anti-inflammatory microenvironment, and glycolysis metabolic regulation in skeletal muscle of db/db diabetic and db/+ non-diabetic mice. Non-diabetic db/+ mice and diabetic db/db mice were randomly assigned to the following groups: db/+CON, db/+DOX, db/dbCON, and db/dbDOX. Mice in db/+DOX and db/dbDOX groups were intraperitoneally injected with DOX at a dose of 15 mg per kg body weight whereas mice in db/+CON and db/dbCON groups were injected with the same volume of saline instead of DOX. Gastrocnemius was immediately harvested, weighed, washed with cold phosphate buffered saline, frozen in liquid nitrogen, and stored at -80 ºC for later analysis. The effects of DOX on diabetic muscle were neither seen in insulin signaling markers (Glut4, pIRS1Ser636/639, and pAktSer473) nor muscle atrophy markers (muscle mass, MuRF1 and MAFbx). However, DOX exposure resulted in enhancement of pro-inflammatory favoring microenvironment (as indicated by TNF-α, HIFα and pNFκBp65) accompanied by diminution of anti-inflammatory favoring microenvironment (as indicated by IL15, PGC1α and pAMPKβ1Ser108). Metabolism of diabetic muscle was shifted to anaerobic glycolysis after DOX exposure as demonstrated by our analyses of PDK4, LDH and pACCSer79. Our results demonstrated that there might be a link between inflammatory modulation and the dysregulation of aerobic glycolytic metabolism in DOX-injured diabetic skeletal muscle. These findings help to understand the pathogenesis of DOX-induced myotoxicity in diabetic muscle.